A comparative study on nanoparticle network‐dependent electrical conductivity, electromagnetic wave shielding effectiveness and rheological properties in multiwall carbon nanotubes filled polymer nanocomposites - Huang, Ming‐Lu; Shi, Yu‐Dong; Wang, Ming (Polymer composites, 2023)
Herein, a comparative study for the effect of nanoparticle networks on rheological behavior, electrical conductivity, and electromagnetic wave (EMW) shielding effectiveness (SE) is carried in conductive polymer composites (CPC). Two different polymers, that is, poly(ε‐caprolactone) (PCL) and isotactic polypropylene (iPP), which have different dispersion of multiwall carbon nanotubes (MWCNT), are used as polymer matrices. A transmission electron microscope (TEM) and a scanning electron microscope (SEM) are employed to determine the dispersion of MWCNTs in different polymer matrices. A rotational rheometer and a vector network analyzer are used to evaluate the percolation thresholds of storage modulus, complex viscosity and EMW SE, respectively. The results indicate that the EMW SE percolation thresholds are much larger than the electrical and rheological percolation thresholds. Specifically, the percolation thresholds of storage modulus and complex viscosity are 0.39 and 0.33 vol% for the MWCNT/PCL samples, and 1.57 and 1.57 vol% for the MWCNT/iPP samples, respectively. The electrical and EMW SE percolation thresholds are 0.33 and 1.99 vol%, 1.24 and 5.41 vol% for the MWCNT/PCL and MWCNT/iPP nanocomposites, respectively. The electrical and rheological percolation may happen in the samples with a sparse MWCNT network, while EMW SE percolation may require a dense MWCNT network in the samples. The MWCNT networks can affect electrical, rheological and EMW shielding properties. The electrical and rheological percolations happen in the samples with a sparse MWCNT network, while EMW SE percolation requires a dense MWCNT network in the samples.